2013
DOI: 10.1136/heartjnl-2013-304394
|View full text |Cite
|
Sign up to set email alerts
|

Stroke prevention by percutaneous closure of patent foramen ovale: a systematic review and meta-analysis

Abstract: Percutaneous closure of PFO in patients with cryptogenic stroke does not appear superior to medical therapy according to currently available randomised data. Furthermore, it is associated with an increased incidence of atrial fibrillation. However, there are signals pointing towards a potential benefit and more research should be strongly encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 34 publications
0
36
0
4
Order By: Relevance
“…Several meta-analyses published over the past decade demonstrated the potential benefit and superiority of PFO closure for preventing stroke recurrence compared with medical therapy alone [16-24]. Results of all included studies demonstrated the superiority of PFO closure compared to medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses published over the past decade demonstrated the potential benefit and superiority of PFO closure for preventing stroke recurrence compared with medical therapy alone [16-24]. Results of all included studies demonstrated the superiority of PFO closure compared to medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…2). This incomplete fusion results in a pouch that, in the majority of instances, communicates with the left atrium cavity [49]. The presence of LASP with access to the systemic circulation also raises the possibility that, similar to the LAA, during low-flow states, this pouch might serve as a site for thrombus formation and embolization.…”
Section: Pouches Of Left Atrial Septummentioning
confidence: 99%
“…[8][9][10] A recent meta-analysis that combined the results of these 3 RCT showed that the weighted incidence of recurrent stroke was 1.7% in the closure group and 2.9% in the best medical therapy group. 14 The relative risk for stroke was lower after PFO closure (relative risk, 0.66; 95% confidence interval, 0.37-1.19; P=0.171).…”
Section: Association Of Pfo and Cryptogenic Strokementioning
confidence: 99%